Adaptation Entrepreneurship Education Model Curriculum 2013 for SMK (Description Preparation and Implementation Barriers in School)/Model Pendidikan Kewirausahaan Adaptasi Kurikulum 2013 bagi SMK (Diskripsi Persiapan dan Hambatan Penerapan di Sekolah) - Agung Winarno (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2015)
The purpose of this research is the discovery of an effective entrepreneurial education model for SMK to implement the values of character and attention to the nuances of curriculum 2013. This model was developed as a whole better schools, teachers and learning tools and practices of learning activities. Specifically, this study aims to (1) describe the preparation of schools in planning appropriate entrepreneurship education curriculum in 2013 (2) identifies the difficulties that arise in the context of the transition adjustments from the previous curriculum leading to the curriculum in 2013 (3) collate and find draft model of entrepreneurship education character-based.The results showed that there was no significant change related to the implementation of the curriculum in 2013, changes occur in the process of adaptation of teachers to understand the curriculum, especially on the subjects of craft and Entrepreneurship are not yet fully have terstandart syllabus. In general, teachers are also still doubts over the implementation of the guidance curriculum which is based on 2013, this is caused understanding core competencies both spiritual and social attitudes as learning indirect to direct instructional coloring on behavioral aspects of competency knowledge there has been no agreement, in addition to almost all teachers yet have adequate syllabus including the media and materials. The model is offered in the study related to the development of curriculum and learning tools that are integrated with a comprehensive system of entrepreneurship education both regarding the function of institutions (schools) and teacher qualifications. Abstrak : Tujuan penelitian ini adalah ditemukannya   model pendidikan kewirausahaan yang efektif bagi  SMK dengan mengimplementasikan nilai-nilai karakter dan memperhatikan nuansa kurikulum 2013. Model ini dikembangkan secara menyeluruh baik sekolah, guru maupun perangkat pembelajarannya serta praktik-praktik kegiatan pembelajaran. Secara khusus penelitian ini bertujuan untuk (1) mendiskripsikan persiapan sekolah didalam menyusun perencanaan pendidikan kewirausahaan sesuai  kurikulum 2013 (2) mengidentifikasi kesulitan-kesulitan yang timbul dalam rangka transisi penyesuaian dari kurikulum sebelumnya menuju ke kurikulum 2013 (3) menyusun dan menemukan draf model pendidikan kewirausahaan berbasis karakter.Hasil penelitian menunjukkan bahwa tidak terdapat perubahan yang berarti terkait dengan penerapan kurikulum 2013, perubahan terjadi pada proses adaptasi para guru untuk memahami kurikulum terutama pada mata pelajaran Prakarya dan Kewirausahaan yang belum secara lengkap memiliki silabus terstandart. Pada umumnya para guru  juga masih ragu atas implementasi yang dilakukan berdasarkan tuntunan  kurikulum 2013, ini terjadi disebabkan pemahaman Kompetensi Inti baik sikap spiritual dan  sosial sebagai pembelajaran tidak langsung untuk mewarnai pembelajaran langsung pada aspek kompetensi pengetahuan perilaku belum terdapat kesepahaman, selain itu hampir semua guru juga belum memiliki Silabus yang memadai termasuk media dan bahan ajarnya. Model yang ditawarkan dalam penelitian ini terkait dengan pengembangan kurikulum dan perangkat pembelajarannya yang terintegrasi dengan sistem menyeluruh pendidikan Kewirausahaan baik menyangkut fungsi kelembagaan (Sekolah) maupun  kualifikasi guru.